Intestinal CD8+ tissue‐resident memory T cells: From generation to function. Issue 10 (29th August 2022) - Cheng, Liqing; Becattini, Simone
Abstract: Tissue‐resident memory T cells (Trm), and particularly the CD8 + subset, have been shown to play a pivotal role in protection against infections and tumors. Studies in animal models and human tissues have highlighted that, while a core functional program is shared by Trm at all anatomical sites, distinct tissues imprint unique features through specific molecular cues. The intestinal tissue is often the target of pathogens for local proliferation and penetration into the host systemic circulation, as well as a prominent site of tumorigenesis. Therefore, promoting the formation of Trm at this location is an appealing therapeutic option. The various segments composing the gastrointestinal tract present distinctive histological and functional characteristics, which may reflect on the imprinting of unique functional features in the respective Trm populations. What these features are, and whether they can effectively be harnessed to promote local and systemic immunity, is still under investigation. Here, we review how Trm are generated and maintained in distinct intestinal niches, analyzing the required molecular signals and the models utilized to uncover them. We also discuss evidence for a protective role of Trm against infectious agents and tumors. Finally, we integrate the knowledge obtained from animal models with that gathered from human studies. Abstract : Tissue‐resident memory T cells are key players in protection from infectious agents and tumors at multiple anatomical locations. Here, we review the current knowledge about gut‐resident CD8 + T cells, discussing the ontogeny, phenotype, and functions of these cells across the entire length and distinct tissue layers of the intestinal tract.